Effect of liquidity, profitability, and size of companies on firm value - RESCHIWATI, R.; SYAHDINA, A.; HANDAYANI, S. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to examine and analyze the effect of liquidity, profitability, the size of the firm and its value in capital structure. The sample in this study was 15 banking companies listed on the Indonesian Stock Exchange in the 2014-2018 period. The method of analysis used was Eviews 8.0 program. The results of this study indicate that liquidity, profitability, and firm size significantly influence capital structure. Capital structure is not a mediator of the influence of liquidity and profitability on firm value, while the capital structure is a mediator of the effect of firm size on firm value.RESUMEN Este estudio tiene como objetivo examinar y analizar el efecto de la liquidez, la rentabilidad, el tamaño de la empresa y su valor en la estructura de capital. La muestra en este estudio fueron 15 compañías bancarias que cotizan en la Bolsa de Indonesia en el período 2014-2018. El método de análisis utiliza el programa Eviews 8.0. Los resultados de este estudio indican que la liquidez, la rentabilidad y el tamaño de la empresa influyen significativamente en la estructura del capital. La estructura de capital no es un mediador de la influencia de la liquidez y la rentabilidad en el valor de la empresa.